Challenges to Accessing and Utilizing Adolescent Sexual and Reproductive Health and Rights Services in Rwanda - Habtu M; Rutayisire E; Nisengwe S; Nikwigize S; Asingizwe D; Dodoo N; Ntakirutimana T (Journal of Multidisciplinary Healthcare, 2025)
Michael Habtu,1 Erigene Rutayisire,1 Simonie Nisengwe,2 Solange Nikwigize,1 Domina Asingizwe,3 Naa Dodoo,4 Theoneste Ntakirutimana1 1School of Public Health, College of Medicine and Health Sciences, University of Rwanda, Kigali, Rwanda; 2Single Project Implementation Unit, University of Rwanda, Kigali, Rwanda; 3School of Health Sciences, College of Medicine and Health Sciences, University of Rwanda, Kigali, Rwanda; 4African Institute for Development Policy (AFIDEP), Lilongwe, MalawiCorrespondence: Michael Habtu, Email mikel.habtu@gmail.com Erigene Rutayisire, Email rerigene@gmail.comBackground: Adolescents in Rwanda, like in other developing countries in Africa, continue to face challenges in accessing and using sexual and reproductive health and right (SRHR) services despite recent progress. They lack accurate information about sexual health, which increases the risk of unplanned pregnancies, sexually transmitted infections, premature death, and unsafe abortions. Thus, our study aimed to explore the challenges that adolescents face in accessing and utilizing SRHR services in Rwanda.Methods: This was a qualitative, phenomenological study. Twelve focus group discussions among in-school and out-of-school adolescents and 36 key informant interviews with stakeholders involved in SRHR service delivery were conducted. Data were collected using semi-structured interviews and discussion guides, supported by audio recordings and field notes. The data were analyzed using a deductive thematic analysis approach, structured around the Social Ecological Model. The analysis was conducted using Atlas ti. Version 8 software.Results: The study revealed five themes of challenges aligned with the socio-ecological model framework: intrapersonal level (fear of being judged and stigmatization), interpersonal level (poor parent-adolescent communication and parents’ lack of knowledge about SRHR), institutional level (judgmental attitude of the providers, shortages of ARSHR service providers, unsupportive environment, and long distance), community level (socio-cultural taboos and religious norms), and policy level (parental consent requirement for ASRHR access).Conclusion: This study identified several challenges, including individual, interpersonal, institutional, community, and policy related factors. Therefore, comprehensive and multimodal interventions are needed to address the various challenges that limit adolescents’ access to and utilization of SRHR information and services.Keywords: adolescent sexual and reproductive health and rights, access, challenges, Rwanda, utilization